Infliximab for the treatment of pyoderma gangrenosum: a randomised, double blind, placebo controlled trial. Issue 4 (27th September 2005) - Brooklyn, T N; Dunnill, M G S; Shetty, A; Bowden, J J; Williams, J D L; Griffiths, C E M; Forbes, A; Greenwood, R; Probert, C S
Abstract : Background: Pyoderma gangrenosum (PG) is a chronic ulcerating skin condition that often occurs in association with inflammatory bowel disease. There have been a number of reports of PG responding to infliximab, a monoclonal antibody against tumour necrosis factor α. Aim: In the first randomised placebo controlled trial of any drug for the treatment of PG, we have studied the role of infliximab in this disorder. Subjects: Patients 18 years of age or older with a clinical diagnosis of PG were invited to take part. Methods: Patients were randomised to receive an infusion of infliximab at 5 mg/kg or placebo at week 0. Patients were then assessed at week 2 and non-responders were offered open labelled infliximab. The primary end point was clinical improvement at week 2, with secondary end points being remission and improvement at week 6. Results: Thirty patients were entered into the study. After randomisation, 13 patients received infliximab and 17 patients received placebo. At week 2, significantly more patients in the infliximab group had improved (46% (6/13)) compared with the placebo group (6% (1/17); p = 0.025). Overall, 29 patients received infliximab with 69% (20/29) demonstrating a beneficial clinical response. Remission rate at week 6 was 21% (6/29). There was no response in 31% (9/29) of patients. Conclusions: This study has demonstrated that infliximab at a dose of 5 mg/kg is superior to placebo in the treatment of PG. Open label treatment with infliximab also produced promising results. Infliximab treatment should be considered in patients with PG.